Routine malaria vaccination in Africa: a step toward malaria eradication? - Olivier Sibomana; John Bukuru; Sulymon A. Saka; Marie Grace Uwizeyimana; Alex Mwangi Kihunyu; Abraham Obianke; Samuel Oluwo Damilare; Lewis Tem Bueh; Beloved of God Agbelemoge; Richard Omoefe Oveh (Malaria Journal)
Abstract Malaria remains a significant global health challenge, with nearly half of the world's population at risk of infection. In 2022 alone, malaria claimed approximately 608,000 lives, with 76% of these fatalities occurring in children under the age of five, underscoring the disease’s disproportionate impact on vulnerable populations. Africa bears the highest burden, accounting for 94% of global malaria cases. For over 60 years, the development of a malaria vaccine has been a critical objective for scientists and governments, with substantial efforts directed toward this goal. Recent progress has led to the approval of the first malaria vaccines, RTS,S/AS01 (Mosquirix®) and the R21/Matrix-M vaccine. Inspired by the promise of these vaccines, the global malaria community has renewed its focus on malaria eradication, 50 years after flawed earlier eradication efforts in the mid-twentieth century. Since the World Health Organization’s endorsement of RTS,S in 2021 and R21 in 2023, several African countries, beginning with Cameroon, have integrated these vaccines into routine immunization programmes. This review examines the role of routine malaria vaccination in Africa as a key strategy toward malaria elimination, explores challenges and solutions for widespread vaccine implementation, and discusses future directions in the ongoing fight to eliminate malaria on the continent.